Health-related quality of life in pregnancy with uterine fibroid: a cross-sectional study in China - Ming, Wai-Kit; Wu, Huailiang; Wu, Yanxin; Chen, Hanqing; Meng, Tian; Shen, Yiwei; Wang, Ziyu; Huang, Xinyu; Sun, Weiwei; Chow, Tik Sang; Wang, Yuan; Ding, Wenjing; et al. (Health and quality of life outcomes, 2019)
Uterine fibroids (UFs) are the most common benign tumors in women. They are likely to cause numerous clinical symptoms, such as pain, menorrhagia, and other obstetric complications in pregnant women. This study aimed to determine the health-related quality of life (HRQoL) during pregnancy with uterine fibroids (UF), thus providing a utility-based case value in pregnant women with UF and understanding of whether HRQoL is associated with clinical outcomes in pregnant women with UFs. This study was conducted in a cross-sectional manner. This study was based on questionnaire surveys completed by sequential out- and in-patients and was conducted in a regional university hospital in Guangzhou, China. The EuroQoL five-dimension-five-level (EQ-5D-5 L) questionnaire was used, and demographic data were collected. An electronic record of the clinical outcomes of pregnant women with UF was retrieved from the hospital's electronic medical record system. The association between UF and HRQoL was evaluated by ordered regression. Seven-hundred-sixty-seven pregnant women with a mean age (SD) of 32.7 (4.8) years completed 707 questionnaires. Overall, when comparing the UF with non-UF groups, we detected statistical differences in age, body mass index (BMI), gravidity and abortion times, partner's smoking and alcoholic habits, advanced maternal age, and uterine scars (p <  0.05). Furthermore, pregnant women without UF scored significantly higher than those with UF on the EQ-5D value system (0.84 versus 0.79; p = 0.017). Moreover, pregnant women with UF suffered more health-related problems, especially with respect to self-care (odds ratio [OR] = 3.69, p <  0.01) and usual activity dimensions (OR = 2.11; p = 0.01). We found that UF has a negative impact on the HRQoL of pregnant women with respect to self-care and usual activity dimensions. Also, the EQ-5D score was a better index than the EQ-VAS score for HRQoL when evaluating of the QoL of our population of pregnant women.